CONJUGATE HEAT TRANSFER ANALYSIS OF JET IMPINGEMENT AND FILM COOLING ON LEADING EDGE OF GAS TURBINE BLADE - SHIVAJI LAMANI; DR. YOGANANDA A (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper deals with the numerical analysis of 3d model of a Leading Edge of Nozzle Guide Vane of a Gas turbine Blade, Here we can used the different types of blade materials like Steel,Nickle,Titanium and Inconel.Initiallycompare the computationallyanalysis values and graphs of a Steel to the experimentally values and graphs are matches to each other. The difference is appearance for temperature to non-dimensional blade length is 1k and for the non-dimensionaltemperature to the non-dimensional blade length is 0.06, while compare to experimental and CFD Analysis. Also for the low temperature and high temperature materials, Compare to the thermal analysis for steel,Inconel, Nickel and Titanium materials, The thermal flux is more for Inconel than above given materials. Also the strength of Inconel is better than other materials. However its limitation is weight science its density is more than other materials.